Organizational and legal provision of information security of enterprises - BONDARENKO Наталія; SYTNICHENKO Олена (Ius Modernum, 2023)
Introduction. Within the framework of European integration, the effectiveness of the work of national enterprises depends on the information security, and ultimately the degree of protection of the public interests of the country, the informational rights of people and citizens. Problem. In the conditions of military and informational aggression against Ukraine, it is important to ensure organizational and legal information security of enterprises, which includes the analysis of the legislative framework in this area, as well as the study of personnel who may become a source of information leakage. The aim of the article is to assess the legal regulation of information security of enterprises from the point of view of their organizational component and to determine the threats of information leakage that may be created by the enterprise personnel in connection with access to confidential, secret and official information. Methods. A number of philosophical, general scientific, special scientific principles and methods are used: dialectical, comparative analysis, systemic, analysis and synthesis, formal and legal. Results. Normative and legal regulation of information security in Ukraine is ensured by the Constitution of Ukraine, a number of laws and other normative and legal documents. In order to eliminate dangers and threats to the company’s activity, it is necessary to analyse the external and internal environment of its activity and eliminate factors of a destructive nature. In this context, it is important to control the access of employees to work with documents and materials that contain information with limited access. Corporate ethics is also an important tool. Conclusions. Ukraine managed to achieve certain successes in terms of normative and legal regulation of information security, although a number of shortcomings remained. The use of modern personnel technologies allows enterprises to ensure information security. Employees who are guilty of disclosing information that is a commercial secret, in accordance with Part 6 of Art. 36 of the Civil Code of Ukraine bear responsibility established by law – disciplinary, material, civil, administrative or criminal. An important element of information security of enterprises is control, which is entrusted to its security service.